2018
DOI: 10.1007/s10103-018-2510-0
|View full text |Cite
|
Sign up to set email alerts
|

Photobiomodulation effects on mRNA levels from genomic and chromosome stabilization genes in injured muscle

Abstract: Muscle injuries are the most prevalent type of injury in sports. A great number of athletes have relapsed in muscle injuries not being treated properly. Photobiomodulation therapy is an inexpensive and safe technique with many benefits in muscle injury treatment. However, little has been explored about the infrared laser effects on DNA and telomeres in muscle injuries. Thus, the aim of this study was to evaluate photobiomodulation effects on mRNA relative levels from genes related to telomere and genomic stabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Experimental animal research (Table 3) supports the beneficial effects of PBM applied before and after exercise in physical activity, through improved performance in endurance training [78,79], decreased level of proinflammatory cytokines [80][81][82][83][84], positive effects on aerobic metabolism [85,86], oxidative stress [86][87][88] and increased ATP [89,90]. Histopathological examination performed after PBM showed that it can protect myonecrosis, reduce pro-inflammatory cell infiltration, muscle destruction, inflammation and can help accelerate tissue repair [91][92][93].…”
Section: Discussionmentioning
confidence: 83%
“…Experimental animal research (Table 3) supports the beneficial effects of PBM applied before and after exercise in physical activity, through improved performance in endurance training [78,79], decreased level of proinflammatory cytokines [80][81][82][83][84], positive effects on aerobic metabolism [85,86], oxidative stress [86][87][88] and increased ATP [89,90]. Histopathological examination performed after PBM showed that it can protect myonecrosis, reduce pro-inflammatory cell infiltration, muscle destruction, inflammation and can help accelerate tissue repair [91][92][93].…”
Section: Discussionmentioning
confidence: 83%
“…Previous studies have demonstrated modulation of mRNA levels from shelterin complex genes after exposure to a low-power infrared laser [ 23 , 24 ]. These lasers are considered safe and effective nonionizing sources with well-established photobiomodulation effect on cells and tissues in the so-called therapeutic window [ 25 , 26 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a study, it was demonstrated that exposure to a low-power infrared laser increases the mRNA levels of TRF1 and TRF2 genes in myoblasts, which can conibute to telomere stabilization [ 23 ]. In another study, mRNA relative levels of TRF1 and TRF2 genes were modulated by a low-power infrared laser in injured skeletal muscle in an experimental model of muscle injury [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation